The Joined Cases Aranyosi and Căldăraru: A New Limit to the Mutual Trust Presumption in the Area of Freedom, Security, and Justice? - Bovend'Eerdt, Koen (Utrecht Journal of International and European Law, 2016)
In this case, the CJEU answers the question whether Article 1(3) of the Framework Decision on the European arrest warrant must be interpreted as meaning that when there are strong indications that detention conditions in the issuing Member State infringe Article 4 of the Charter, the executing judicial authority must refuse surrender of the person against whom a European arrest warrant is issued. The CJEU rules that if, after a two-stage assessment, the executing judicial authority finds that there is a real risk of an Article 4 violation for the requested person once surrendered, the execution of the arrest warrant must initially be deferred and, where such a risk cannot be discounted, the executing judicial authority must decide whether or not to terminate the surrender procedure. This conclusion shakes the system of mutual trust upon which the principle of mutual recognition is built.